Training to Teach in Further and Adult Education - Gray, David E. (David Edward), 1952-; Griffin, Colin; Nasta, Tony. (Cheltenham : Nelson Thornes, 2005)
Written for all those who are training to teach in further and adult education, this text will be of use to anyone working in this rapidly changing sector.
Previous ed.: Cheltenham: Stanley Thornes, 2000.
Includes bibliographical references (p. 293-297) and index.
Keywords: Adult Learning -- Great Britain; College teaching -- Great Britain; Adult education teachers -- Great Britain; Education